Visionary Leadership in Islamic Education: Transforming Practices and Enhancing Educational Governance - Manaf, Sofwan; Novita, Mona; Rokimin; At Thaariq, Zahid Zufar (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to explore the crucial role of visionary leadership in transforming educational practices within Islamic educational institutions. The research employed a qualitative method, incorporating a literature review and secondary data analysis, which began with a review of relevant journals on leadership in Islamic education. The author collected and analyzed several articles related to visionary leadership, educational governance, and the challenges faced by Islamic educational institutions in the era of globalization. The findings indicate that visionary leadership plays a central role in integrating traditional Islamic values with modern innovations, significantly enhancing educational quality, fostering community engagement, and ensuring the sustainability of Islamic educational institutions. This leadership also supports effective change management, the application of technological innovations, and the development of leadership models based on ethical principles and Islamic teachings. Furthermore, the internal and external challenges faced by leaders require adaptability, innovation, and strategic resource management to maintain the relevance of institutions in an increasingly interconnected world. This study implies that the effective implementation of visionary leadership, supported by key factors such as institutional image-building, relevant curriculum development, and strategic management practices, is essential for improving the effectiveness and sustainability of Islamic education.